Pageants and processions : images and idiom as spectacle - Du Toit, Herman C. (Cambridge Scholars, 2009)
Nowadays pageants often take the form of parades of effervescent young women competing for popular recognition in hyped up media events. However, these "beauty pageants" are a mere pastiche of the elaborate historical parades of the medieval period that took significant, social, religious, or civic events and their protagonists, as subjects. Pageants were historically characterized by resplendent costuming and elaborate processions that were often given to much pomp and ceremony. Pageantry ha...